CRISPR/Cas9-mediated mutagenesis of homologous genes in Chinese kale - Sun, Bo (Sci Rep, 2018)
The clustered regulatory interspaced short palindromic repeat-associated protein 9 (CRISPR/Cas9) system has developed into a powerful gene-editing tool that has been successfully applied to various plant species. However, studies on the application of the CRISPR/Cas9 system to cultivated Brassica vegetables are limited. Here, we reported CRISPR/Cas9-mediated genome editing in Chinese kale (Brassica oleracea var. alboglabra) for the first time. A stretch of homologous genes, namely BaPDS1 and BaPDS2, was selected as the target site. Several stable transgenic lines with different types of mutations were generated via Agrobacterium-mediated transformation, including BaPDS1 and BaPDS2 double mutations and BaPDS1 or BaPDS2 single mutations. The overall mutation rate reached 76.47%, and these mutations involved nucleotide changes of fewer than 10 bp. The clear albino phenotype was observed in all of the mutants, including one that harbored a mutation within an intron region, thereby indicating the importance of the intron. Cleavage in Chinese kale using CRISPR/Cas9 was biased towards AT-rich sequences. Furthermore, no off-target events were observed. Functional differences between BaPDS1 and BaPDS2 were also assessed in terms of the phenotypes of the respective mutants. In combination, these findings showed that CRISPR/Cas9-mediated targeted mutagenesis can simultaneously and efficiently modify homologous gene copies of Chinese kale and provide a convenient approach for studying gene function and improving the yield and quality of cultivated Brassica vegetables.